KELOMPOK USAHA BERSAMA PENGRAJIN SUTERA MANDAR DI DESA KARAMA KECAMATAN TINAMBUNG KABUPATEN POLEWALI MANDAR PROVINSI SULAWESI BARAT - B., Indayani; Qamariah, Nur; Fitri, Nurul (Departemen Budidaya Pertanian Fakultas Pertanian UNHAS, 2020)
Mandar silk crafts is a creative industry that utilizes the basic ingredients of silk that are processed into a piece of cloth that can be sarong, shirt, shawl and etc. One of the Mandar silk artisants is in the Karama village, Tinambung subsdistrict, Polewali Mandar district. The Area manages the Mandar silk sarong commonly known by the term